ANALISIS HUKUM TINDAK PIDANA PERDAGANGAN SATWA DILINDUNGI MENURUT UU NO. 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSITEMNYA” (Studi di Balai Besar Konservasi Sumber Daya Alam Sumatera Utara) - Maswita Maswita (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
This study aims to find out the background of  illegal trade of the protected animals that still happening continuously  and how is the role of the government through the Natural Resources Conservation Center of Sumatera Utara in dealing with criminal acts of trafficking in protected animals in accordance with the Law No. 5 of 1990 concerning conservation and biological natural resources and their ecosystems. This study was conducted at Natural Resources Conservation Center of Sumatera Utara. The method used in this study is a literature study. Interviews were conducted with the officials from the Natural Resources Conservation Center of Sumatera Utara. The results of this study indicate that the trade in protected animals continues due to the lack of government supervision in this case the Natural Resources Conservation Center, high animal prices, easy access to the technology and high buyer interest. Keywords : Criminal Acts, Animal Trade